2013
DOI: 10.1093/ntr/ntt073
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Adverse Maternal and Child Health Outcomes in Brazil

Abstract: The results show that over a 20-year period, during which Brazil implemented numerous effective tobacco control measures, the country experienced a dramatic decrease in both maternal smoking prevalence and smoking-attributable adverse MCH outcomes. Countries that implement effective tobacco control measures can expect to reduce both maternal smoking and adverse MCH outcomes, thereby improving the public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 44 publications
4
32
1
1
Order By: Relevance
“…Our literature review 23 found that PTB tend to be underdiagnosed and underreported. However, their measurement improved in 2011, when gestational age began to be collected in exact weeks and not grouped into categories 24 .…”
Section: Extension Of the Model: Incorporating Smoking-attributable Bmentioning
confidence: 85%
See 2 more Smart Citations
“…Our literature review 23 found that PTB tend to be underdiagnosed and underreported. However, their measurement improved in 2011, when gestational age began to be collected in exact weeks and not grouped into categories 24 .…”
Section: Extension Of the Model: Incorporating Smoking-attributable Bmentioning
confidence: 85%
“…To avoid overlap, we excluded PTB from LBW cases. Since reliable data for adverse MCHOs were not available before 2000, we estimated trends in years prior to 2000 from the published literature on an outcome-by-outcome basis 23 , yielding an increasing trend for PTB and a decreasing trend for SIDS between 1989 and 2000, but no trend for LBW and placenta praevia/placental abruption.…”
Section: Extension Of the Model: Incorporating Smoking-attributable Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria for definition of life-threatening conditions, namely gestational age less than 32 weeks, birth weight less than 1,500g, or five-minute Apgar score less than seven (pragmatic criteria for definition of near miss 9 ), correspond to adverse perinatal outcomes and are associated with sociodemographic variables 13 reproductive history, risk behavior 1,18 , and prenatal, delivery, and neonatal care 2,9,19 . Our results corroborated previous studies on factors associated with adverse neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Tal associação já foi verificada em coorte estadunidense ao se verificar associação entre IMC >30 kg/m² e os nascimentos prematuros por indicação médica, com OR de 1,4 nas gestações entre a 34ª e 36ª semana e de 1,7 nas anteriores à 34ª semana gestacional 16 . Em relação ao uso do tabaco, mesmo não se encontrando associação significativa com a prematuridade, é possível observar que há uma elevação na taxa de gestantes tabagistas no local de estudo (13,3% no grupo Caso) quando comparada à média nacional (7,7%) 17 . Ainda, é importante salientar a taxa de gestantes consideradas fumantes passivas (57%).…”
Section: Discussionunclassified